Wybrane wykładniki intensywności cechy określanej przymiotnikiem "piękny" w prasie codziennej po 1989 roku. Analiza korpusowa = Some indicators of intensity of the quality named by the adjective "beautiful" in the daily press after 1989. Corpus-based analysis - Szymańska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The corpus-based analysis presented in this paper includes selected aspects of the functioning of the adjective "piękny" ("beautiful"), connected with evaluating and referring to the aesthetic category, in the daily press after 1989.
Keywords: wykładniki intensywności; stopień przymiotnika; przysłówki stopnia; gramatyka konstrukcji; analiza korpusowa; indicators of intensity; degree of an adjective; adverbs of degree; Construction Grammar; corpus-based analysis